2010
DOI: 10.1155/2010/798069
|View full text |Cite
|
Sign up to set email alerts
|

Structural Health Monitoring System Using Piezoelectric Networks with Tuned Lamb Waves

Abstract: Abstract. The paper presents a structural health monitoring system based on propagation of tuned Lamb waves and their interference with discontinuities. The dispersion curves are studied to determine the appropriate type and dimension of transducers and to select the optimum scanning frequencies and relevant propagation modes. A piezoelectric sensor network was implemented in an aluminum plate in order to generate and to sense the wave propagation and associated reflections. The algorithm developed for damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…If a simple sine wave composed of a few cycles is emitted then the desired frequency can be actuated; however, the frequency domain of such a signal shows small secondary peaks in the frequency domain that are present at other frequencies. To eliminate these peaks the signal can be modulated with a window function to slowly increase and decrease the magnitude of the signal [18]. A commonly used signal that provides a good compromise between number of cycles and ramp up rate consists of five sine peaks modulated by a Hann window.…”
Section: Theory and Implementationmentioning
confidence: 99%
“…If a simple sine wave composed of a few cycles is emitted then the desired frequency can be actuated; however, the frequency domain of such a signal shows small secondary peaks in the frequency domain that are present at other frequencies. To eliminate these peaks the signal can be modulated with a window function to slowly increase and decrease the magnitude of the signal [18]. A commonly used signal that provides a good compromise between number of cycles and ramp up rate consists of five sine peaks modulated by a Hann window.…”
Section: Theory and Implementationmentioning
confidence: 99%
“…It was suggested that the maximum excitation and detection of a particular Lamb wave mode can be achieved when the length of the transducer equals half of its wavelength. This behaviour is generally referred to as Lamb wave tuning as a transducer can be designed to be sensitive to a particular wave mode and almost completely insensitive to another wave mode at the same frequency [10]. Figure 4 shows this effect for a 7 mm long piezoelectric transducer and 2 mm thick aluminium sheet, where the strain response of the transducer with respect to the wave modes can be seen for different values of frequency [11].…”
Section: Aementioning
confidence: 99%
“…One of the most investigated approaches to develop SHM system is based on excitation of elastic waves by a network of piezoelectric transducers (PZTs) integrated with the monitored structure. 2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Elastic waves can propagate significant distances, and they are sensitive to local structure discontinuities and deformations. Thus, by virtue of their nature, they can be used for damage detection, irrespective of the type of the material used for aircraft manufacturing.…”
Section: Introductionmentioning
confidence: 99%